Analysis of Twitter User Responses to the Aqua Billboards Series #DiRumahAJa - Agy Firda Sandi; Arif Ardy Wibowo; Rahina Nugrahani; Roziani Mohd Nasir (Universitas Ahmad Dahlan, 2022)
Advertising is a marketing communication to promote or sell a product with several purposes and characteristics. There are two characteristics of it, commercial and non-commercial advertising, such as public service advertisement. Public service advertisement aims to inform a message of public importance. A mineral water company, AQUA, has made a public service advertisement about Covid-19. AQUA use billboard as the media to inform message to the public. This billboard has been a hot topic on social media, especially on Twitter. The aftermath of this billboard is incredible. Users on Twitter do interact with this billboard picture. This research aims to analyze users' sentiment about this billboard. The author uses a descriptive qualitative method in this research. The author collects the data from Twitter directly, taking a screenshot of each user's response to the billboard picture. The author collects all responses and categorizes the responses into positive, negative, and neutral. The author uses a programming language, Python, to obtain a graphic for research needs, and the result is analyzed with Sentiment Analysis theory. The result shows that positive responses are more significant with 73.2%.